CHANGING WORDS BY CASES, GENDERS, NUMBERS, SPELLING RULES - Наврузова Фарида Назаровна (Modern American Journals, 2025)
The article discusses the main grammatical categories of the Russian language related to the change of words in cases, genders and numbers, as well as the key rules of spelling. The features of inflection in different parts of speech are analyzed, examples are given and the most common spelling difficulties are considered.
Keywords: Case, gender, number, inflection, spelling, grammar, spelling